ChemInform Abstract: Urea‐Based Porous Organic Frameworks: Effective Supports for Catalysis in Neat Water. Issue 35 (2nd September 2014) - Li, Liuyi; Chen, Zhilin; Zhong, Hong; Wang, Ruihu
Abstract Two urea‐based porous organic frameworks are synthesized through an urea‐forming condensation of benzenetriisocyanate with 1, 4‐diaminobenzene and benzidine, respectively.